Identification of two novel linear epitopes on the E165R protein of African swine fever virus recognized by monoclonal antibodies - He, Jian; Li, Jieqiong; Luo, Mingzhan; Liu, Yangkun; Sun, Jingchen; Yao, Lunguang (Frontiers in Veterinary Science, 2024)
African swine fever (ASF) is a highly fatal infectious disease in pigs, caused by the African swine fever virus (ASFV). It is characterized by short disease duration and high morbidity and mortality. In August 2018, ASF was first reported in China and it subsequently spread rapidly throughout the country, causing serious economic losses for the Chinese pig industry. Early detection plays a critical role in preventing and controlling ASF because there is currently no effective vaccine or targeted therapeutic medication available. Additionally, identifying conserved protective antigenic epitopes of ASFV is essential for the development of diagnostic reagents. The E165R protein, which is highly expressed in the early stages of ASFV infection, can serve as an important indicator for early detection. In this study, we successfully obtained high purity soluble prokaryotic expression of the E165R protein. We then utilized the purified recombinant E165R protein for immunization in mice to prepare monoclonal antibodies (mAbs) using the hybridoma fusion technique. After three subclonal screens, we successfully obtained three mAbs against ASFV E165R protein in cells named 1B7, 1B8, and 10B8. Through immunofluorescence assay (IFA) and Western blot, we confirmed that the prepared mAbs specifically recognize the baculovirus-expressed E165R protein. By using overlapping truncated E165R protein and overlapping peptide scanning analysis, we tentatively identified two novel linear B cell epitopes ( 13 EAEAYYPPSV 22 and 55 VACEHMGKKC 64 ) that are highly conserved in genotype I and genotype II of ASFV. Thus, as a detection antibody, it has the capability to detect ASFV across a wide range of genotypes, providing valuable information for the development of related immunodiagnostic reagents.